Self-Determination Theory and the Emerging Fields of Relationship Science and Niche Construction Theory – a Review Essay - Martos, Tamás; Sallay, Viola (European Journal of Mental Health, 2017)
In this paper we summarise the basic tenets of Self-Determination Theory (SDT). As a special occasion for this overview, we review two recently published edited books on relationship motivation (WEINSTEIN 2014) and work motivation (GAGNÉ 2014) because both of them rely extensively on SDT concepts and principles while they extend the conceptual frames of the theory to several directions and applied fields. Furthermore, we argue that the basic propositions of SDT may contribute to the emerging field of the so called Relationship Science, the continuously forming interdisciplinary knowledge base on close relationships. On the other hand we propose that SDT could and should be further enriched by broader system theoretical approaches. Therefore we outline the evolutionary theoretical principles of human agency as represented in Niche Construction Theory and its applications in social sciences. While a complete theoretical integration exceeds the frames of a review, we draw a series of conclusions that may point in this direction.